Pengaruh Pendapatan Asli Daerah (PAD) dan Penanaman Modal Dalam Negeri (PMDN) Terhadap Pendapatan Domestik Regional Bruto (PDRB) Provinsi Jawa Barat Tahun 2012-2018 - Citra Rhamadani; Febriana Agatasya; Misfi Laili Rohmi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research aims to examine the influence of Regional Original Income (PAD) and Domestic Investment (PMDN) on the Gross Regional Domestic Product (GRDP) of West Java Province during 2012-2018. A quantitative approach is used as an analysis method. GRDP data was obtained from BPS and the SPSS 26 approach was used for data analysis. The research results show that partially PAD has a significant influence on GRDP, while PMDN does not have a significant influence on GRDP. Meanwhile, results were simultaneously obtained that PAD and PMDN had a significant effect on the GRDP of West Java Province 2012-2018.